The CCL2 synthesis inhibitor bindarit targets cells of the neurovascular unit, and suppresses experimental autoimmune encephalomyelitis - Ge, Shujun (BioMed Central, 2012)
BACKGROUND: Production of the chemokine CCL2 by cells of the neurovascular unit (NVU) drives critical aspects of neuroinflammation. Suppression of CCL2 therefore holds promise in treating neuroinflammatory disease. Accordingly, we sought to determine if the compound bindarit, which inhibits CCL2 synthesis, could repress the three NVU sources of CCL2 most commonly reported in neuroinflammation – astrocytes, microglia and brain microvascular endothelial cells (BMEC) – as well as modify the clinical course of neuroinflammatory disease. METHODS: The effect of bindarit on CCL2 expression by cultured murine astrocytes, microglia and BMEC was examined by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Bindarit action on mouse brain and spinal cord in vivo was similarly investigated by qRT-PCR following LPS injection in mice. And to further gauge the potential remedial effects of bindarit on neuroinflammatory disease, its impact on the clinical course of experimental autoimmune encephalomyelitis (EAE) in mice was also explored. RESULTS: Bindarit repressed CCL2 expression by all three cultured cells, and antagonized upregulated expression of CCL2 in both brain and spinal cord in vivo following LPS administration. Bindarit also significantly modified the course and severity of clinical EAE, diminished the incidence and onset of disease, and evidenced signs of disease reversal. CONCLUSION: Bindarit was effective in suppressing CCL2 expression by cultured NVU cells as well as brain and spinal cord tissue in vivo. It further modulated the course of clinical EAE in both preventative and therapeutic ways. Collectively, these results suggest that bindarit might prove an effective treatment for neuroinflammatory disease.